Creative City Brand Building on Social Media Platforms - Wang, Qixuan (International Journal of Global Economics and Management, 2024)
With the advent of the digital age, social media has become an important tool to shape the image of a city’s brand. This paper aims to explore how to use social media platforms to build creative city brands, so as to enhance the attractiveness and competitiveness of cities. Through the study of many successful cases at home and abroad, combined with the theory of social media communication and the theory of urban brand image, this paper analyzes the mechanism of social media in urban brand promotion. The research adopted a combination of quantitative and qualitative methods, including online questionnaire survey, social media data analysis and in-depth interviews, to collect and analyze relevant data. The results show that social media can not only increase the visibility of cities, but also promote cultural exchanges and economic cooperation. In addition, the study found that personalized content creation, interactive user engagement, and sustained brand storytelling are key factors for successful city branding on social media. Finally, this paper puts forward suggestions on social media marketing strategies for different types of cities, and points out that future research should pay attention to the impact of changes in social media platform algorithms on the effectiveness of urban brand communication. This study provides a practical reference for city managers to promote city image more effectively in the new media environment.